2000
DOI: 10.1007/s005860000140
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical dimensions of the lower lumbar vertebrae - analysis of data from digitised CT images

Abstract: IntroductionAccurate and comprehensive anthropometric data for the lumbar spine vertebrae, a frequent site for implantation surgery, are incomplete at present. Information on the precise dimensions of the lower lumbar vertebrae is, however, essential, for the rational design and development of spinal implants and instrumentation such as pedicle screws and, in particular, with the evolution towards robotic surgery. Previous studies have depended on direct measurements from plain X-ray films [9,12,13,23], or fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 30 publications
11
128
0
Order By: Relevance
“…A recent study showed that currently available lumbar disc prostheses are much smaller than lumbar endplates regarding anteroposterior and mediolateral diameter [17]. From a biomechanical point of view, an implant with the largest possible surface area appears best to avoid subsidence into the vertebral body, as the circumference would provide a brace for the strongest areas in the periphery [18]. Inadequate endplate design can equally contribute to subsidence as a result of extremely concentrated stress [2].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that currently available lumbar disc prostheses are much smaller than lumbar endplates regarding anteroposterior and mediolateral diameter [17]. From a biomechanical point of view, an implant with the largest possible surface area appears best to avoid subsidence into the vertebral body, as the circumference would provide a brace for the strongest areas in the periphery [18]. Inadequate endplate design can equally contribute to subsidence as a result of extremely concentrated stress [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, the morphological reconstruction of the disc space in fossils is difficult due to the intrinsic variation in this region and the lack of preservation. Measurements of the intervertebral height of the modern spine revealed a remarkable range of variation, suggesting that disk height is highly variable and therefore difficult to predict [18]. To our knowledge no data are available on Neanderthal disc space/ inter-vertebral height.…”
Section: Morphology Of the Spinementioning
confidence: 95%
“…Adjacent segments have been studied using different techniques [radiography, computed tomography (CT), magnetic resonance imaging (MRI)] [6,20,29,38]. Disc height has been described as indicator of disc degeneration and regeneration [26,31].…”
Section: Introductionmentioning
confidence: 99%